Primary intra medullary inter locking nailing for open tibia fractures a prospective analysis of functional and radiological outcome - Ali, Mohamed Ashraf; Adimoolam, Manikandan; Banu, Haseena (International Journal of Research in Orthopaedics, 2021)
Background: Tibia is the most commonly fractured long bone in the body encountered in today’s practice. The use of non-operative treatment of tibial fractures is associated with a high prevalence of malunion, joint stiffness and poor functional outcome. This study was conducted to analyze the functional and radiological outcome of patients treated for open fractures of tibia with primary intramedullary interlocking nailing within 24 hours of injury. Methods: From October 2013 to May 2015, a prospective and descriptive study was done where 30 consecutive patients with open tibial fractures was treated with primary intramedullary interlocking nailing within 24 hours of injury, at Pondicherry institute of medical sciences, Pondicherry. Functional outcome was assessed using Karlstrom and Olerud scores and radiological outcome was assessed by radiographic union scale of tibial fractures (RUST) scores at 6 weeks, 3rd, 6th, 9th and 12th month post-operatively. Intra-operative and post-operative complications were noted and documented. The results were analyzed using SPSS software. Results: The most common age group who presented was between 18-30 years and the average age was 36.7 years. 36.67% had grade I injury, 40% had grade II injury, meanwhile, grade IIIA injuries constituted 20% and grade IIIB injuries constituted 3.33%. The average functional score was 33.33 which showed overall good result. The average RUST score was found to be 11.33 denoting union. Conclusions:Hence, we observed that intramedullary interlocking nailing is a good procedure in terms of functional and radiological outcome if done within 24 hours of injury.